Effects of Stem Density on Crown Architecture of Scots Pine Trees - Saarinen, Ninni; Kankare, Ville; Huuskonen, Saija; Hynynen, Jari; Bianchi, Simone; Yrttimaa, Tuomas; Luoma, Ville; Junttila, Samuli; Holopainen, Markus; Hyyppä, Juha; Vastaranta, Mikko (Frontiers in Plant Science, 2022)
Trees adapt to their growing conditions by regulating the sizes of their parts and their relationships. For example, removal or death of adjacent trees increases the growing space and the amount of light received by the remaining trees enabling their crowns to expand. Knowledge about the effects of silvicultural practices on crown size and shape as well as about the quality of branches affecting the shape of a crown is, however, still limited. Thus, the aim was to study the crown structure of individual Scots pine trees in forest stands with varying stem densities due to past forest management practices. Furthermore, we wanted to understand how crown and stem attributes as well as tree growth affects stem area at the height of maximum crown diameter (SAHMC), which could be used as a proxy for tree growth potential. We used terrestrial laser scanning (TLS) to generate attributes characterizing crown size and shape. The results showed that increasing stem density decreased Scots pine crown size. TLS provided more detailed attributes for crown characterization compared to traditional field measurements. Furthermore, decreasing stem density increased SAHMC and strong relationships (Spearman correlations >0.5) were found between SAHMC and crown and stem size as well as stem growth. Thus, this study provided quantitative and more comprehensive characterization of Scots pine crowns and their growth potential. The combination of a traditional growth and yield study design and 3D characterization of crown architecture and growth potential can open up new research possibilities.